Interdisciplinary actions in SEPSE situations in the intensive care unit: integrative review - Lima, Wallber Moreno da Silva (2024)
Introduction: Sepsis, also called generalized infection, is an illness that, if not treated early and immediately, spreads quickly throughout the body and affects the immune system, making it difficult for organs to function. Objective: to evaluate interdisciplinary actions in cases of sepsis in the ICU. Methodology: Integrative literature review research, guided by the following steps: construction of the research question; delimitation of inclusion and exclusion criteria; choice of databases; search and selection of studies; analysis and presentation of results.Results and Discussion: 1,990 studies were identified, after applying the language inclusion criterion, remaining 200 studies, and then reading the titles, in which 1,790 articles were excluded, as they were not related to the objective of this article. The abstracts of the 200 articles selected from the analysis of the titles were read and only those that met the inclusion criteria had their abstracts investigated. The research comprised 10 articles. Conclusion: Sepsis occurs due to several factors such as the patient's age, length of stay, pre-established comorbidities, immunity and the procedures performed on the patient.